2023
DOI: 10.1002/cctc.202300716
|View full text |Cite
|
Sign up to set email alerts
|

Desilicated ZSM‐5 Catalysts: Properties and Ethanol to Aromatics (ETA) Performance

Abstract: Herein, desilication in increasingly harsh conditions was used to introduce mesopores into two different industrial ZSM‐5 catalysts (Si/Al ratio 11 or 29). For desilicated samples, increasing BET surface areas, mesopore volumes, and Si(OH) densities were noted. Brønsted acid site (BAS) densities increased upon desilication, as formerly inaccessible BAS in blocked pores became available, while the strength of the BAS was maintained upon desilication. Using KOH instead of NaOH as desilication agent can increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
(165 reference statements)
0
4
0
Order By: Relevance
“…The results presented therein can, for example, be understood if we remember that the authors found mesopores on their catalysts. It was in that recently shown respect that mesoporosity can lead to an increased selectivity to aromatics in the ETA conversion [14]. When it comes to S60/60 in the ETA conversion, herein, the ratio between the different products is not significantly changed, the final coke contents are similar, and the calculated mechanistic descriptors, C 3= /C 3 ratio and HTI, of S60/2 and S60/60 are almost identical.…”
Section: Methanol-to-olefin (Mto) and Ethanol-to-aromatics (Eta) Conv...mentioning
confidence: 57%
See 2 more Smart Citations
“…The results presented therein can, for example, be understood if we remember that the authors found mesopores on their catalysts. It was in that recently shown respect that mesoporosity can lead to an increased selectivity to aromatics in the ETA conversion [14]. When it comes to S60/60 in the ETA conversion, herein, the ratio between the different products is not significantly changed, the final coke contents are similar, and the calculated mechanistic descriptors, C 3= /C 3 ratio and HTI, of S60/2 and S60/60 are almost identical.…”
Section: Methanol-to-olefin (Mto) and Ethanol-to-aromatics (Eta) Conv...mentioning
confidence: 57%
“…This leads to a longer residence time inside larger particles and a changed selectivity during MTO conversion. This explains why post-modifications that enhance the coke resistance of the ZSM-5 catalyst, like mesopore formation, are very promising strategies to increase the lifetime of ETA conversion catalysts [14,18]. Thus, it was herein clarified how one parameter, ZSM-5 crystal size, impacts the ETA product distribution.…”
Section: Methanol-to-olefin (Mto) and Ethanol-to-aromatics (Eta) Conv...mentioning
confidence: 95%
See 1 more Smart Citation
“…They suggested that the introduction of mesoporosity could promote the accessibility of reactants to both Brønsted and Lewis acid sites within the zeolite. Moreover, Dittmann and co-workers revealed that the modified bulk HZSM-5 through combined desilication and dealumination could enhance the accessibility of Brønsted acid sites and increase the density of Si­(OH) species. Although the influence of these Si­(OH) species on deactivation behavior remains unclear, they observed that the rate of coke formation increased as a function of improved Si­(OH) species concentrations.…”
Section: Ethanol-to-aromatic Conversionmentioning
confidence: 99%
“…Comparing the BAS density from TPP loading with the total BAS density of a sample (determined by loading with a smaller probe molecule) enables the quantification of the share of external sites and the quantification of BAS that were introduced by desilication (see Figure ). ,, Also a larger homologue of TPP, tri-( p -methoxyphenyl)­phosphine (TMPP), is unable to access micropores and suited to quantify external BAS on zeolites . Noteworthy, the long T 1 times of free TPP (7.7 ± 0.4 s) and other pure phenylphosphines make far longer delay times in between scans necessary, if all peaks in the spectrum, not only those of TPP on BAS, shall be quantified. , …”
Section: Families Of Solid-state Nmr Probe Moleculesmentioning
confidence: 99%